Weight Bias Internalization Scale: Psychometric properties using alternative weight status classification approaches. (June 2016) - Lee, Morgan S.; Dedrick, Robert F.
Highlights: The WBIS performed similarly based on perceived weight status versus BMI. Removal of Item 1 resulted in a higher Cronbach's alpha in both groupings. Acceptable fit was found for a one-factor model in both groupings. Findings suggest consideration of removal of Item 1 from the WBIS. When using the WBIS, perceived weight status is an acceptable alternative to BMI. Abstract: The Weight Bias Internalization Scale (WBIS) was developed to facilitate systematic investigation of internalized weight bias, but the English version has not undergone confirmatory factor analysis (CFA). Additionally, it is unclear whether the measure can be used when participants are grouped based on self-perceived versus body mass index (BMI)-based weight status. The present study evaluated the WBIS in a sample of 243 male and female undergraduate students who were overweight/obese as classified by self-perception or BMI. After exclusion of Item 1 due to poor item-to-total correlation, Cronbach's alphas were .92 and .94 for the perception-based and BMI-based groupings, respectively. CFAs using the reduced 10-item scale with addition of modifications for correlated errors resulted in acceptable model fit for the one-factor model in both groupings. Findings suggest psychometric properties of the modified WBIS are acceptable and are similar for overweight/obese participants grouped by either perceived weight status or BMI.